Gastric Myoelectrical Activity Patterns and Water‐Load Satiety Test in Patients With Chronic Dyspeptic Symptoms - Uday C. Ghoshal; Mahesh K. Goenka; Uzma Mustafa; Awanish Tewari; Nikhil Sonthalia; Subhamoy Das; Nabaruna Chakraborty; Akash Roy; Shruti Keyal; Sourish Roy (JGH Open, 2025)
ABSTRACT Background/Aims Patients with chronic dyspeptic symptoms may or may not experience nausea and vomiting. Consensus papers suggested that gastroparesis should be defined by symptoms like nausea and vomiting rather than investigations only. Recognizing that gastric dysrhythmias contribute to nausea, vomiting, and maybe a biomarker and therapeutic target, the primary hypothesis of the study was that dyspeptic patients with predominant nausea and vomiting, without mechanical obstruction, would show different gastric myoelectrical activity (GMA) on electrogastrography (EGG) and tolerance to the water‐load satiety test (WLST) than those without these symptoms. The secondary aim was to assess the relationship between GMA, WLST, and demographic and clinical profiles. Methods Data of 660 chronic dyspeptic patients undergoing WLST‐based EGG were retrospectively analyzed. Results Of the 660 patients, 287 (females 158[55%]) experienced nausea with or without vomiting, while 373 (females 151[41%]) did not. Nausea with or without vomiting was significantly associated with female gender, younger age, and weight loss (151[40.5%] vs. 158[55.1%], p < 0.001; 47[36,59] vs. 41[29,55], p < 0.001; 62[16.6%] vs. 85[29.6%], p < 0.001). Patients with nausea with/without vomiting could drink lesser volumes of water compared to those without (500[400,500] vs. 500[450,550], p = 0.007). Gastric dysrhythmia was present in both groups. Normogastric power change was significantly lower in patients with nausea with or without vomiting, compared to those with neither nausea nor vomiting (3.7[−5.5, 11.5] vs. 7.3[−1.7,16], p < 0.001). Conclusions Patients experiencing nausea with or without vomiting have significantly more GMA abnormalities as evidenced by reduced power change in the normogastria range after water intake, and could drink lesser water, compared to patients without these symptoms.